A Bibliometric Study on the Development of Research Related to Tax Compliance Factors in Indonesia - Astagina Naghi, I Wayan Boby; Irawati, Ira; Darto, Darto (E-Jurnal Akuntansi, 2024)
This study aims to identify research trends and map the scholarly discourse on factors influencing tax compliance, with a particular focus on Indonesia. The objective is to provide a deeper understanding of the existing body of knowledge and highlight potential research gaps for future exploration. A total of 23 articles were retrieved from the Scopus database, subjected to specific selection criteria, and analyzed using bibliometric techniques with VOSviewer visualization, alongside a hermeneutic content analysis. The findings indicate that research on factors affecting tax compliance in Indonesia remains relatively limited. Commonly recurring keywords in the literature include ‘tax compliance,’ ‘tax awareness,’ ‘e-filing,’ and ‘tax sanctions.’ In contrast, less frequently studied topics encompass ‘perception of corruption,’ ‘gender,’ ‘religiosity,’ ‘uli'l-amr,’ ‘social norms,’ ‘traditional approach,’ ‘millennials,’ and ‘modernization of tax administration.’ The hermeneutic content analysis identifies four primary clusters of factors influencing tax compliance: taxpayer characteristics, environmental influences, governmental policies, and religiosity. The variation in research keywords, the scope of journal databases, and cross-country comparisons present valuable opportunities for future research directions.